Stagnation point flow of carbon nanotubes over stretching cylinder with slip conditions - Hayat Tasawar; Farooq Muhammad; Alsaedi Ahmed (Open Physics, 2015)
This work concentrates on stagnation point flow of a nanofluid over an impermeable stretching cylinder with mass transfer and slip effects. Carbon nanotubes (CNTs) and water are used as a nanofluid in the present investigation. Two types of CNTs are used as nanoparticles (i) Single-wall carbon nanotubes (SWCNTs) and (ii) multiwall carbon nanotubes (MWCNTs). Appropriate transformations are used to achieve a system of ordinary differential equations. Convergent series solutions are obtained. Behavior of various parameters on the velocity, temperature and concentration profiles are discussed graphically. Numerical values of skin friction coefficient, Nusselt number and Sherwood number are computed and analyzed.